Applicant Perspectives During Selection: A Review Addressing "So What?, " "What's New?, " and "Where to Next?". (July 2017) - McCarthy, Julie M.; Bauer, Talya N.; Truxillo, Donald M.; Anderson, Neil R.; Costa, Ana Cristina; Ahmed, Sara M.
We provide a comprehensive but critical review of research on applicant reactions to selection procedures published since 2000 ( n = 145), when the last major review article on applicant reactions appeared in the Journal of Management. We start by addressing the main criticisms levied against the field to determine whether applicant reactions matter to individuals and employers ("So what?"). This is followed by a consideration of "What's new?" by conducting a comprehensive and detailed review of applicant reaction research centered upon four areas of growth: expansion of the theoretical lens, incorporation of new technology in the selection arena, internationalization of applicant reactions research, and emerging boundary conditions. Our final section focuses on "Where to next?" and offers an updated and integrated conceptual model of applicant reactions, four key challenges, and eight specific future research questions. Our conclusion is that the field demonstrates stronger research designs, with studies incorporating greater control, broader constructs, and multiple time points. There is also solid evidence that applicant reactions have significant and meaningful effects on attitudes, intentions, and behaviors. At the same time, we identify some remaining gaps in the literature and a number of critical questions that remain to be explored, particularly in light of technological and societal changes.